Reproductive and body size measurements in a cohort of Roan- and Sable antelope (Hippotragus equinus- and niger) in South Africa - Koeppel, Katja Natalie (University of Pretoria, 2021)
Dissertation (MAgric (Animal Production Management))--University of Pretoria. 2020.